Tourism and Protected Areas: The Guadiana Valley Natural Park, Portugal - FIGUEIRA, Victor; ROLHA, João; SOUSA, Bruno; VAREIRO, Laurentina (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022, 2022)
Sustainability is a topic that is currently being discussed and constantly adapting, since it is related not only to an ecologically correct posture and strategy but also economically viable and socially equitable. The present manuscript intends to understand and analyze tourism and protected areas in Portugal, namely the case of the Guadiana Valley Natural Park (Portugal). This paper presents theoretical considerations that aim to understand how “protected areas” can become a destination for future sustainable tourism trips. In the end, the limitations of the study and guidelines for future research will be presented.